Mechanism of tobacco-sweet potato intercropping in suppressing Ralstonia solanacearum in flue-cured tobacco - Yang, Liqian; Liu, Yang; Guo, Shiping; Li, Tong; Nie, Qiuyue; Zhang, Yonghui; Zeng, Shuhua; Wang, Fei; Liu, Lei (Frontiers in Plant Science, 2025)
Tobacco bacterial wilt (Ralstonia solanacearum) is a fatal pathogen of tobacco, causing severe losses annually. Intercropping has been proposed as a sustainable strategy to mitigate soil-borne pathogens through rhizosphere interactions. However, the mechanisms by which tobacco-sweet potato intercropping specifically affects the microecological environment and suppresses R. solanacearum remain poorly understood. To investigate the effect of the TSP model on the soil-borne pathogen of bacterial wilt (Ralstonia solanacearum) in tobacco-growing soil, this study compared and analyzed the characteristics and differences in bacterial wilt incidence, Ralstonia solanacearum content, phenolic acid components, metabolome, and metagenome between (T) and (TSP) systems. The results showed that compared to the T treatment, the TSP treatment reduced the incidence of bacterial wilt in flue-cured tobacco and significantly decreased the abundance of R. solanacearum in the soil by 21.4%, while increasing the total phenolic acid content by 21.9%. The total phenolic content in the TSP soil was increased by 21.9% compared to T. Differentially abundant metabolites between TSP and T were primarily enriched in carbohydrate metabolic pathways, such as nucleotide sugar biosynthesis, fructose, and mannose metabolism. The content of substances such as rhamnose, D-allose, and mannitol in T-treated soil was 2.14–6.62 times higher than that in TSP-treated soil, with new tobacco alkaloids being up to 91.09 times higher. Compared to the T treatment, the TSP treatment significantly increased the relative abundances of Acidobacteriota, Chloroflexota, Bradyrhizobium, Pseudolabrys, and Sphingomonas by 64.08%, 18.86%, 23.55%, 21.80%, and 12.98%, respectively. The content of Ralstonia solanacearum in the soil was positively correlated with differential metabolites such as mannitol, rhamnose, and D-allose (r = 0.8), while negatively correlated with phenolic acids such as syringic acid, ferulic acid, caffeic acid, and gallic acid, as well as microorganisms such as Chloroflexota, Gemmatimonadota, Acidobacteriota, and Sphingomonas. In summary, TSP can regulate soil metabolites, phenolic acids, and beneficial microorganisms, forming a synergistic network to suppress the content of Ralstonia solanacearum and reduce the risk of tobacco bacterial wilt. This provides a theoretical basis for regulating soil microecology and enhancing crop disease resistance in intercropping systems.